Metal halide perovskite: a game-changer for photovoltaics and solar devices via a tandem design. Issue 1 (31st December 2018) - Shen, Heping; Duong, The; Wu, Yiliang; Peng, Jun; Jacobs, Daniel; Wu, Nandi; Weber, Klaus; White, Tom; Catchpole, Kylie
Abstract: Multi-junction tandem design has been proven to be an effective means to further improve the efficiency of solar cells. However, its share in the photovoltaics market at present is tiny, since the most efficient tandem device comprises III-V semiconductors, which entail the use of expensive fabrication processes. The advent of perovskite solar cells, which have revitalized the PV field with their unprecedented pace of development, promises to address this bottleneck. Perovskite materials could not only serve as the top subcell absorber for commercial solar cells including Si and copper indium gallium selenide, but could work efficiently as bottom subcells owing to highly tuneable bandgaps which extend down to the range of 1.2 to 1.5 eV. The highest-efficiency perovskite tandem to date was achieved by pairing a perovskite top cell with a Si bottom cell in a four-terminal configuration, yielding 26.4%. This review gives an overview of recent progress on the main tandem structures, and describes the detailed design improvements that have resulted in new record efficiencies. Ultimately, commercialization of these tandem solar cells relies on the scalability of perovskite technology. We, therefore, highlight the development of large-scale tandems and approaches to produce perovskite modules. We also point out the critical aspects that will require further effort and provide guidelines for future developments. The potential obstacles that will hamper the commercialization of perovskite tandems, if not adequately addressed, namely device stability and toxicity, are then critically examined. Finally, the substantial opportunities that perovskite materials open up for other solar devices with a tandem configuration are mentioned, which are attracting increasing attention. Abstract :